Environmental assessment of magnesium oxychloride cement samples : a case study in Europe - Kastiukas, Gediminas (2021)
This study is the first in the literature to systematically assess the environmental impacts of magnesium oxychloride cement (MOC) samples, which are regarded as a more eco-friendly construction material than Portland cement. The environmental impacts of MOC samples prepared with various molar ratios of MgO/MgCl2∙6H2O and sources of reactive magnesia were obtained via a life cycle assessment (LCA) approach (from cradle to grave), and the obtained outcomes were further compared with the counterparts associated with the preparation of Portland cement (PC) samples. Meanwhile, a sensitivity analysis in terms of shipping reactive magnesia from China to Europe was performed. Results indicated that the preparation of MOC samples with higher molar ratios led to more severe overall environmental impacts and greater CO2 sequestration potentials due to the difference of energies required for the production of MgO and MgCl2∙6H2O as well as their various CO2 binding capacities, whereas in terms of CO2 intensities, the molar ratios in MOC samples should be carefully selected depending on the strength requirements of the applications. Furthermore, various allocation procedures and MgO production processes will greatly influence the final outcomes, and allocation by mass is more recommended. Meanwhile, the environmental impacts associated with the transportation of reactive magnesia from China to Europe can be ignored. Finally, it can be concluded that MOC concrete is no longer a type of ‘low-carbon’ binder in comparison with PC concrete in terms of CO2 emissions, and in view of the single scores and mixing triangles for weighing, MOC concrete can only be identified as a type of more sustainable binder than PC concrete when the main component MgO in MOC samples is obtained through the dry process route rather than the wet process route.